Reconstructing polyaromatic hydrocarbons degrading pathways in the enriched bacterial consortium and their biosurfactants characterization. Issue 2 (April 2022) - Ibrar, Muhammad; Yang, Xuewei
Abstract: Due to substantial metabolic burden and low carbon fluxes, a single microorganism cannot utilize multiple classes of hydrocarbons typically found in the polluted environment. A microbial consortium comprising biosurfactants producing strains and hydrocarbon degradative strains could have promising bioremediation capabilities. To address this question, bacteria from non-contaminated soil were enriched in a medium containing polyaromatic hydrocarbons. The metabolic potential and pathways of PAHs degrading bacterial consortia (CON-PAH) that drive energy and carbon from PAHs assimilation were elucidated by metagenomic analysis. CON-PAH degrade more than 90% of PAHs (naphthalene, phenanthrene, and pyrene) with concomitant biosurfactants production. Tween-20 and glucose as a co-substrate suppress the PAHs degradation. Six high-quality metagenome-assembled genomes (MAGs) were assembled with an estimated size of 3.8–6.5 Mb from metagenomic data of CON-PAH. The draft genome of Deliftia tsuruhatensis and Pseudomonas putida contain the entire benzoate and near-complete naphthalene and phenanthrene degradation pathways. For the first time, we reconstruct PAH degrading pathway in D. tsuruhatensis sp. The metagenomic reconstruction of bins indicates the cross-feeding of bacteria within the consortium and suggests that complete PAH degradation pathways may not be obligatory for individual bacteria in the consortium. Biosurfactants structure elucidation via LC/MS showed lipopeptide containing the heptapeptides with different lipid moieties. This work will deepen our understanding of the metabolic capacity of microbial communities and provide new ideas for the engineering of artificial microbial consortia. Graphical Abstract: ga1 Highlights: Minimal medium containing hydrophobic compounds is a practical approach for isolating biosurfactants and biodegradative bacteria. Non-contaminated soil bacteria have the intrinsic ability to degrade polyaromatic hydrocarbons. Reconstruction of near complete PAHs degrading pathway in Deliftia tsuruhatensis and Pseudomonas putida sp. Tween-20 and glucose as a co-substrate suppress the PAHs degradation.